The effect of the Super Set muscle endurance exercises in some physical abilitiesand the achievement of 800 meters advanced - أ. ابتسام حيدر أ. د. أسراء فؤاد أ. د. سهاد قاسم (physical education and sport sciences college for women/ Baghdad University, 2018)
This study aimed to identify the effect of endurance exercises in the development of some physical abilities and achievement of the race running 800 meters advanced, the researchers hypothesized the existence of a positive effect of the training of muscle endurance of the Super Sit in the 800 meters, the researchers used the experimental approach  for its suitability with nature of the research included the research sample The experimental group used the experimental method for the super sit exercises for muscular endurance. The control group used the traditional method of training. The homogeneity and equivalence between the two groups was carried out. (10) weeks, and (3) training units in each week and in a time not exceeding (30-40) minutes from the main section of the training unit. Some statistical treatments were used for this purpose (the arithmetic mean) , The mean deviation, the torsion coefficient, the median, and the T test). The results of the study showed that there were significant differences between some variables such as bearing speed, carrying speed, strength and achievement level in the sample of experimental group members. Maximum speed Yen groups in the post test.